Creating National Poverty Profiles and Growth Incidence Curves with Incomplete Income or Consumption Expenditure Data: An Application to Bolivia - Julius Spatz; Stephan Klasen; Melanie Grosse (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
In many developing countries, there does not exist a time series of nationally representative household budget or income surveys, while there often are surveys of regions as well as nationally representative Demographic and Health Surveys (DHS) which lack information on incomes. This makes an analysis of trends and determinants of poverty and inequality impossible. This is also the situation in Bolivia where there exist urban household surveys and nationally representative DHS since 1989, while nationally representative household income surveys only exist since 1997. In this paper, we adjust a technique developed for poverty mapping exercises to link urban household income surveys with DHS data to generate a time series of household income data from 1989 to 2002. Our technique performs well on validation tests, is superior to imputing incomes from assets in the DHS, and is able to generate new information on poverty and inequality in Bolivia.
Keywords: D31; I31; O54; C81; I32; 330; Microsimulation; survey matching; poverty; inequality; pro-poor growth; poverty profile; growth incidence curve; Bolivia